ChemInform Abstract: Improvement of the Energy Transfer from Ca3SnSi2O9 Host to Rare‐Earth Ions with the Assistance of Oxygen Vacancies. Issue 20 (20th May 2014) - Yu, Xue; Wang, Ting; Xu, Xuhui; Jiang, Tingming; Yu, Hongling; Jiao, Qing; Zhou, Dacheng; Qiu, Jianbei
Abstract Eu3+‐doped Ca3SnSi2O9 is prepared via solid state synthesis using stoichiometric mixtures of CaCO3, CaF2, SnO2, SiO2, Eu2O3, and Dy2O3 with small amounts of H3BO3 as flux (1400 °C, 4 h, ambient atmosphere).